2017
DOI: 10.1002/2016je005234
|View full text |Cite
|
Sign up to set email alerts
|

South Pole Aitken Basin magnetic anomalies: Evidence for the true polar wander of Moon and a lunar dynamo reversal

Abstract: The analysis of the Lunar Prospector magnetic data over South Pole Aitken basin reveals two categories of magnetic anomalies with distinctly different polarities. Modeling the anomalies in terms of vertical prism source bodies shows two separate true polar wander paths of the Moon. One is driven by the giant surface mass deficiency resulted from the formation of the South Pole Aitken basin and the other by the giant surface mass concentrations (mascons) formed inside the large impact basins, such as Serenitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 87 publications
(141 reference statements)
0
7
0
Order By: Relevance
“…Here, we explore equatorial surface field values of 0.5, 2, and 5 μT and ultimately will show that paleomagnetic fields of these strengths have considerable effects on the solar wind H + surface flux. As for the orientation of the ancient dynamo, numerous recent studies have shown that the dynamo axis may not have been steady in time (Arkani-Hamed & Boutin, 2017;Baek et al, 2019;Nayak et al, 2017;Oliveira & Wieczorek, 2017;Takahashi & Tsunakawa, 2009). Hence, we model the field as a centered dipole oriented in the +Z SSE direction (parallel to the lunar spin axis) and also as a dipole perpendicular to the spin axis, in the +X/+Y SSE plane.…”
Section: Geophysical Research Lettersmentioning
confidence: 99%
“…Here, we explore equatorial surface field values of 0.5, 2, and 5 μT and ultimately will show that paleomagnetic fields of these strengths have considerable effects on the solar wind H + surface flux. As for the orientation of the ancient dynamo, numerous recent studies have shown that the dynamo axis may not have been steady in time (Arkani-Hamed & Boutin, 2017;Baek et al, 2019;Nayak et al, 2017;Oliveira & Wieczorek, 2017;Takahashi & Tsunakawa, 2009). Hence, we model the field as a centered dipole oriented in the +Z SSE direction (parallel to the lunar spin axis) and also as a dipole perpendicular to the spin axis, in the +X/+Y SSE plane.…”
Section: Geophysical Research Lettersmentioning
confidence: 99%
“…Though anorthositic rocks contain low abundances of metallic iron (e.g., Fuller & Cisowski, 1987), most of these regions are associated with low field strengths, especially when viewed in the magnetic field intensity plot of Figure 1 that uses a linear scale. Thermal evolution models predict that the highland crust would cool entirely below the Curie temperature of metallic iron (1038 K, Dunlop & Özdemir, 2015) within the first 100 Myr of lunar evolution (e.g., Arkani-Hamed & Boutin, 2017;Laneuville et al, 2017). Furthermore, most thermal evolution models predict that the core could have driven a dynamo powered by thermal convection during the first couple hundred million years (e.g., Evans et al, 2014;Konrad & Spohn, 1997;Laneuville et al, 2014;Scheinberg et al, 2015).…”
Section: Origin and Timing Of Crustal Magnetizationmentioning
confidence: 99%
“…The present consensus is that many, if not all, of the Moon's crustal magnetic anomalies formed in the presence of an ancient dynamo field (e.g., Arkani-Hamed & Boutin, 2017;Hood et al, 2017;Nayak et al, 2017;Oliveira & Wieczorek, 2017;Takahashi et al, 2014;Weiss & Tikoo, 2014;Wieczorek, 2018). However, the geologic formation mechanism for any of these anomalies has yet to be established.…”
Section: Introductionmentioning
confidence: 99%